A Sustainable Hybrid Off-Grid System Design for Isolated Island Considering Techno-Economic and Frequency Stability Analysis - Candra Febri Nugraha; Lukman Subekti; Ahmad Adhiim Muthahhari; Budi Eko Prasetyo; Rizki Firmansyah Setya Budi (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Electrifying remote islands presents complex challenges. Currently, most remote areas in Indonesia rely on diesel fuel for their electricity supplies, contributing to escalating generation costs and environmental degradation. Aligned with the global net-zero emission goal, this study proposes the design of a hybrid off-grid system for Kabare Village in the Raja Ampat Islands, integrating techno-economic and frequency stability analyses. HOMER Pro was employed to identify the most optimal system configuration, while DIgSILENT PowerFactory was utilized to assess the frequency stability performance of the system. This study unveils that the optimal system combines existing generators, solar panels, and batteries, with a net present cost of $1.37 million. The optimal system delivers an 11.8% reduction in levelized cost of energy to $0.269/kWh, alongside a 25.6% decrease in both fuel consumption and greenhouse gas emissions compared to the existing system. Moreover, the system meets frequency stability metrics, even under extreme operational conditions. This study demonstrates that implementing a hybrid off-grid system in Kabare Village is not only technically and economically feasible but also a practical option. These findings are anticipated to assist the government in promoting the utilization of renewable energy sources, particularly in remote areas such as the islands of eastern Indonesia.